2021
DOI: 10.4103/jehp.jehp_407_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diabetic foot risk among diabetic patients in a tertiary care hospital, South India

Abstract: INTRODUCTION: Foot problems are most common among patients with diabetes, and they are an important cause of morbidity in patients with diabetes mellitus (DM). They can be prevented by following a simple foot care practice. The study objective was to stratify the level of risk for diabetic foot ulcer (DFU) among patients with diabetes by screening. MATERIALS And METHODS: A descriptive cross-sectional study design was adopted in this study. The sample size was 196, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
1
9
0
1
Order By: Relevance
“…Studies found in the study among DFUs majority of the participants were unaware regarding the foot care practice. [ 4 13 ] This study also confirmed better foot care practices among DWFUs.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Studies found in the study among DFUs majority of the participants were unaware regarding the foot care practice. [ 4 13 ] This study also confirmed better foot care practices among DWFUs.…”
Section: Discussionsupporting
confidence: 72%
“…Dr Akila et al . [ 4 ] in 2020 assessed the diabetic foot risk among 196 diabetes patients. Fifty seven percent of the patients were in the age group 40-60 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that the instrument tool was easy and uncomplicated to use as well as having a manual provided. The reliability depends primarily on good standardization (Woldemariam et al, 2020) and instructions being easy to understand (Akila et al, 2021). Another possible explanation is that the risk factors were objective which influenced reliable scores or outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Poverty and lack of education lead to the usage of inappropriate footwear and late presentation of foot lesions. [7]. Hence this study is an effort in closing the gap in knowledge of the barriers and facilitators specific to Indian population.…”
Section: Introductionmentioning
confidence: 99%